Brachial Plexus Block For Upper Limb Surgery Coracoid Infraclavicular Approach versus Axillary Approach- A Comparitive Study - Parvez Akhtar; Supratim Dasgupta; Priyadershini Rangari (Academia Anesthesiologica International, 2019)
Background: Peripheral nerve blocks (PNBs) have an increasingly important role in ambulatory anesthesia and have many characteristics of the ideal outpatient surgical anesthesia with prolonged postoperative analgesia, and facilitated discharge. Objectives: The aim of our study is to compare brachial plexus block performed by the Axillary and the Coracoid infraclavicular routes using a peripheral nerve stimulator as regard block performance time, onset of sensory block, motor block intensity, block duration and success and failure rates.Subjects and Methods:Our study comprised 40 adult patients of either sex t divided into two groups each 20 patients: Coracoid group and Axillary group were included. A 40 ml mixture of equal parts of 0.5% bupivacaine and 2% lidocaine was used as the local anesthetic material for all the patients of both groups.Results:The axillary approach to the brachial plexus using four injections of the local anesthetic material resulted in a faster onset and fewer incomplete blocks than the coracoid approach using two injections. The axillary approach was also less painful and more comfortable to the patient and resulted in more intense motor block and provided a longer duration of block allowing for longer duration of anesthesia and postoperative analgesia. The coracoid approach had an advantage over the axillary that it can be done with the arm in the neutral position, which is important for patients with an arthritic or stiff shoulder joint.Conclusion: The axillary approach to the brachial plexus using four injections technique resulted in a faster onset of block and a better spread of analgesia and longer duration of anesthesia than the coracoid approach using two injections technique.